ANALYSIS OF DUST GASES FORMATION AND DISPERSE COMPOSITION IN SUPERPHOSPHATE PRODUCTION PROCESS - Nargizakhon Rajabova; Oybek Soliyev (Western European Studies, 2023)
The article presents the results of the research on the development of the methodology for calculating the hydraulic resistance of the dispersion composition analysis of the selected dust samples to determine the cleaning efficiency of the combined scrubber. The error of laboratory analysis between sieve and microscopy method was 5.4%. In the experimental studies conducted to determine the efficiency of cleaning in the scrubber, the average median size of crushed particles for superphosphate dust was taken as d50=9.3 μm
Keywords: combined scrubber; superphosphate dust; sieve analysis